Interaction between anemia and hyperuricemia in the risk of all-cause mortality in patients with chronic kidney disease - Lu, Zhaoxuan; Lu, Fangping; Zhang, Ruixue; Guo, Shuting (Frontiers in Endocrinology, 2024)
Aim: Both hyperuricemia and anemia are not only the manifestation of chronic kidney disease (CKD), but also related to its occurrence and development. A recent study has found there was a synergetic effect between hyperuricemia and anemia on new-onset CKD. Herein, we aimed to explore the roles of hyperuricemia and anemia in the allcause mortality in patients with CKD.Methods: Data of adult patients with CKD were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2009-2018 in this retrospective cohort study. Weighted univariate and multivariate COX regression analyses were used to investigate the associations of hyperuricemia and anemia with all-cause mortality, and the evaluation indexes were hazard ratios (HRs) and 95% confidence intervals (CIs). The interaction effect between hyperuricemia and anemia on the risk of all-cause mortality was assessed via relative excess risk due to interaction (RERI) and attributable proportion of interaction (AP). Subgroup analyses of age, gender, CVD, hypertension, DM, and cancer were also performed to assessed this interaction effect.Results: Among 3,678 eligible patients, 819 died from all cause. After adjusting for covariables, we found that CKD patients with anemia [HR=1.72, 95%CI: (1.42-2.09)]or hyperuricemia [HR=1.21, 95%CI: (1.01-11.45)] had higher risk of all-cause mortality. There was a potential synergetic effect between anemia and hyperuricemia on all-cause mortality, with the RERI of 0.630 and the AP of 0.291. Moreover, this synergetic effect was also observed in ≥65 years old (AP=0.330), male (AP=0.355), Anemia and hyperuricemia in CKD prognosis 3 hypertension (AP=0.736), non-hypertension (AP=0.281), DM (AP=0.371), and cancers (AP=0.391) subgroups.A potential synergetic effect between anemia and hyperuricemia on allcause mortality was found in patients with CKD. However, further studies are needed to clarify the causal relationship between them.